The Effect of BMT Management On Performance To Distribute Productive Financing In Small Business Sectors In Cirebon - Abdul Aziz (UIN Siber Syekh Nurjati Cirebon, 2019)
The rising of the sharia cooperative performance as the objective of sharia cooperative management that required for the improvement of financing productive distribution and empowerment of small business trade sector. The fundamental problems faced by the small business trade sector in Indonesia are the lack of access to capital sources and the weak the role of financial institutions services. Microfinance institutions which be expected tend to more dominant in consumptive financing rather than productive financing. While sharia microfinance institutions do not act optimally. Not yet know how the contribution of the sharia cooperative management in development sharia cooperative performance and its effect in increasing productive financing distribution to empower small business trade sector in Cirebon City and Regency. This study used the explanatory method to explain the causal relationships in the model of empowerment of small business trade sector through hypothesis testing. Data compiled in the form of cross-sectional between a unit of analysis in Cirebon City and Regency. The research model is formulated as a recursive model an analyzed using path analysis. The finding of the study was: (1) the good management governance of funding, membership and financing had significant in increasing sharia cooperative performance. And management of membership proven ineffective and very means in enacting excellence sharia cooperative performance. (2) the sharia cooperative performance has dramatized the increase means, but not yet effective on sharia cooperative performance in financing distribution of Murabaha. (3) the financing distribution of Musyarakah by sharia cooperative performance had a significant effect. (4) the existence sharia cooperative performance very helpful for small business trade sector, mainly in productive financing distribution (Murabahah and Musyarakah).